Internet Usage and Economic Growth: The Case of Mexico - Hsing, Yu; Morgan, Yun-Chen; Phillips, Antoinette S.; Phillips, Carl (Yayasan Ahmar Cendekia Indonesia, 2020)
This paper finds that more internet users as a percentage of total population promote economic growth in Mexico and that the impact exhibited a nonlinear relation and was greater in the initial stage of Internet adoption. In addition, less government budget deficit as a percent of GDP, a higher real stock price, real peso appreciation, a higher real crude oil price or a lower expected inflation rate would enhance economic growth.